Masyarakat Adat Dayak dan Penanggulangan Transboundary Haze Pollution di Kalimantan Barat - Adhi Cahya Fahadayna; Reza Triarda; Jovanka Mayank Candri (Jayapangus Press, 2023)
This research will explore the role and involvement of the indigenous people, the Dayak Tribe, in resolving the problem of wildfire and transboundary haze pollution. This article's case study will focus on Kapuas Hulu, Kalimantan Barat. The research aims to explain indigenous people's participation in resolving transboundary haze pollution in West Borneo. This article will use qualitative methods and a descriptive approach. Data collection and analysis will be done through 1) observation to map the actors involved in resolving transboundary haze pollution, 2) interviews with actors affected by transboundary haze pollution, and 3) assessment to clarify data and secondary sources from the government. The research concludes that the involvement of the Dayak People as an indigenous tribe in West Kalimantan is relatively minimum in solving the transboundary haze pollution. Government programs focusing on transboundary haze pollution should engage with Indigenous tribes actively and deliberately.